DETECTION OF SINGLE NUCLEOTIDE POLYMORPHISM OF A1/A2 VARIANTS OF BETA CASEIN GENE IN UMBALACHERY CATTLE BY TETRA ARMS PCR - R. Kalai Nila; K. Brindha; Y. Krishnamohan Reddy; D. Baskaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Milk is one of the primary protein diets of high biological value available to the human population. As bovine beta casein gene is highly polymorphic with functional implications, this study was designed to detect the beneficial A2 genotype in the native Umbalachery cattle breed. Genomic DNA was isolated from blood samples of Umbalachery cows and A1 and A2 variants were detected by Tetra ARMS polymerase chain reaction. It was observed that the A2A2 genotype frequency was 82% and that of A1A2 was 18%. The A1A1 genotype was not detected in Umbalachery cattle in the present study. It may be concluded that majority of the Umbalachery cows retain their original beta casein protein variant that produce safer A2 milk for human consumption and that Tetra ARMS PCR is an efficient and rapid method that allows detection of single nucleotide polymorphism of A1 and A2 variants of beta casein gene.